Two nostratic etymologies - Alemko Gluhak (Linguistica, 1984)
1. *qamA "dry, warm" In my earlier paper I reconstructed the Nostratic word *qamA "dry, warm"; this etymological nest can be enlarged with some new examples: AA: Sem. *hmm "to be warm": Hebr. hām "warm", Ugar. hm, Syr. hammīmā, Akkad. emmu, Arab. hāmm; Eg. bmm "to be warm, to be hot" , Kopt. (Saĭd.) hmom "to become warm”;